Efficacy and Safety of Anti-HER2 Agents in Combination With Chemotherapy for Metastatic HER2-Positive Breast Cancer Patient: A Network Meta-Analysis - Zhang, Xiaohui; Leng, Junsheng; Zhou, Yidong; Mao, Feng; Lin, Yan; Shen, Songjie; Sun, Qiang (Frontiers in Oncology, 2021)
Background The presence of anti-HER2 agents, such as trastuzumab, pertuzumab, and trastuzumab emtansine (T-DM1), significantly improved the prognosis of metastatic HER2-positive (HER2+) breast cancers (BC). However, drug resistance and disease progression are still common. In order to further improve the treatment efficacy, new clinical trials about anti-HER2 agents in combination with chemotherapy are growing rapidly. We conducted the network meta-analysis to synthesize evidences of clinical trials to identify the best therapy for metastatic HER2+ BC. Methods A systematic search of randomized controlled trials regarding anti-HER2 agents in combination with chemotherapy for advanced or metastatic breast cancers up to May 2020 was conducted in Embase, PubMed, and the Cochrane Library. The primary outcome was progression-free survival (PFS). The secondary outcomes were overall survival (OS), objective response rate (ORR), and safety. Bayesian network meta-analysis was conducted to synthesize the results and rank the therapies. Results Twenty-six studies, including 16 studies for first-line treatments and 10 studies for second- or later-line treatments were included in the network meta-analysis. For first-line studies, the THP (taxanes + trastuzumab + pertuzumab) regimen exhibited the highest probability to be the optimal treatment in all efficacy outcomes and moderate safety. For second- or later-line studies, the T-DM1 and XHTuC (capecitabine + trastuzumab + tucatinib) regimens ranked top two in all efficacy outcomes according to the surface under the cumulative ranking (SUCRA) results. T-DM1 ranked first in PFS and OS whereas XHTuC ranked first in ORR. The safety outcomes of T-DM1 and XHTuC were acceptable. Conclusions THP was still the optimal first-line treatment for metastatic HER2+ BC. T-DM1 and XHTuC were recommended for second-line treatments. Systematic Review Registration INPLASY.com, identifier (INPLASY202090086).